FOREGROUNDING AND COHESION IN PHILIP LARKIN'S POEM 'THE NORTH SHIP' - Muhammad Rifqi (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2010)
This article discusses 'The North Ship', a poem written by Philip Larkin. The poem was examined by using stylistic approachproposed by Leech and Short. Stylistic study is a field of empiricalenquiry in that linguistic theories are used to analyze literary text(Leech and Short; 1994 and 1996). Considering that stylistics deals with a very broad area, this study is limited in two aspects namely foregrounding and cohesion. The whole lines of 'The North Ship' were examined line by line to find out foregrounding techniques used by its writer. Any linguistic features such as diction were classified. Likewise, the poetic features of the poem were identified. Both linguistic and poetic features were then analyzed and described based on the given theory. In addition, the cohesive devices in the poem were identified and traced. They were described one by one based on the classification given in Halliday and Hasan Model. The ties among them were described and showed in the cohesive links and chains Based on the analysis of foregrounding and cohesion, the interpretation of the poem was finally made. The findings showed that foregrounding and cohesion are very supportive each other in creating meaning of the examined poem.Keywords: cohesive devices, deviation, foregrounding, , parallelism, stylistics,